Step-wise Computational Analysis of Kinematics of 3 – Links Articulated Robotic Manipulator - Obasi, C. C.; Ikharo, A. B.; Ogbikaya, S.; Balogun, V. A.; Odaba, A.; Ogbewey, L. I. (Advanced Aspects of Engineering Research Vol. 8, 2021)
This paper presents a computational analysis of the kinematics of a three-link articulated robotic manipulator. The geometric location of the linking arms is used in the design of robot manipulators, which necessitates precise computational study. In order to estimate the robotic arm's location with respect to relation lengths and angle, the angle needed to shift the end effector to a desired position was measured and calculated using the Forward Kinematics and Inverse Kinematics methods. Using free body diagrams and computational estimation of the necessary parameters, a three-link robotic arm with a rigid rotational base was also demonstrated. The results of forward kinematics show that the robot end effector location can be determined using the values of x, y, and z coordinates, allowing for more precise monitoring and adaptation of the robot's arm/motion to its environment.